2022
DOI: 10.1002/dta.3260
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing detection of erythropoietin receptor agonists from dried blood spots for anti‐doping application

Abstract: The World Anti-Doping Agency (WADA) has recently implemented dried blood spots (DBSs) as a matrix for doping control. However, specifications regarding the analysis of the class of prohibited substances called erythropoietin (EPO) receptor agonists (ERAs) from DBSs are not yet described. The aim of this study was to find optimal conditions (sample volume and storage) to sensitively detect endogenous erythropoietin (hEPO) and prohibited ERAs from DBSs and compare detection limits to WADAstipulated minimum requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…The reason for low/absent uEPO signals in the samples and/or low EPO serum levels can be due to diluted urine, sample manipulation, and EPO doping. However, we did not see any correlation with SG, which was surprising, but in line with our previous finding that the intra‐individual variation (CV %) of uEPO did not depend on SG 35 . Notably, the two samples with highest SG showed an absence of uEPO signal, which is in agreement with Lamon et al who reported that both low and high SG were over‐represented in undetectable samples 36 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The reason for low/absent uEPO signals in the samples and/or low EPO serum levels can be due to diluted urine, sample manipulation, and EPO doping. However, we did not see any correlation with SG, which was surprising, but in line with our previous finding that the intra‐individual variation (CV %) of uEPO did not depend on SG 35 . Notably, the two samples with highest SG showed an absence of uEPO signal, which is in agreement with Lamon et al who reported that both low and high SG were over‐represented in undetectable samples 36 …”
Section: Discussionsupporting
confidence: 92%
“…However, we did not see any correlation with SG, which was surprising, but in line with our previous finding that the intra-individual variation (CV %) of uEPO did not depend on SG. 35 Notably, the two samples with highest SG showed an absence of uEPO signal, which is in agreement with Lamon et al who reported that both low and high SG were over-represented in undetectable samples. 36 There are some limitations with the study using self-reported AAS users, including uncontrolled AAS intake in regard to doses, substances, and durations.…”
Section: Discussionsupporting
confidence: 90%
“…It was discovered that a blood volume of 60 µL allowed the detection of ERAs at levels comparable to WADA's minimum required performance levels (MRPLs) described for 500 µL of serum or plasma. 37 In another study, CERA was demonstrated to be detected in DBS using a simple enzyme-linked immunosorbent assay with a screening time of just 2 h. 38 Furthermore, a multi-analyte assay was developed and the performance of several non-volumetric (Whatman cards-Treated: Whatman FTA DMPK-A, Whatman FTA DMPK-B;…”
Section: Sports Anti-dopingmentioning
confidence: 99%
“…A recent critical review by Thevis et al described the advances, potential future perspectives and limitations of blood microsamples in doping controls 157 . Fast and cost‐effective screening methods to detect erythropoietin receptor agonists such as CERA, BRP, NESP and EPO‐Fc using dried blood microsamples were developed and optimised 37,38 . In the study conducted by Heiland et al, different blood sample volumes (20–180 µL) and storage temperatures (−20 to 37°C) were evaluated to determine optimal conditions for detecting prohibited ERAs from DBS.…”
Section: Applicationsmentioning
confidence: 99%
“…Aiming at expanding ERA analytical approaches to DBSs as test matrix, Heiland et al presented an optimized protocol that specifically addressed storage conditions and sample volume for DBSs using different sampling materials 56 . Upon immunopurification, extracts from DBSs formed from formerly 60 μl of whole blood were found to allow for LODs of 62.5, 62, 31, and 12.6 pg/ml for the continuous EPO receptor activator CERA, EPO‐Fc, the European Pharmacopoeia Biological Reference Preparation (BRP) for EPO, and novel erythropoiesis stimulating protein NESP, respectively.…”
Section: Peptide Hormones Growth Factors Related Substances and Mimeticsmentioning
confidence: 99%